An Analysis of Students’ Errors in Writing Recount Text - Hani Mastura; Syamsul Bahri Ys; Masrizal Mahmud (Universitas Syiah Kuala, 2022)
This research attempted to find the types of errors produced by students at the second grade of MTsN in Aceh Besar based on the surface strategy taxonomy and communicative effect taxonomy. It aimed at analysing errors produced by the students in their recount writing based on the surface strategy taxonomy classification which is omission, addition, misformation, and misordering, and communicative effect taxonomy which is local error and global error. This study is done by using quantitative approach. The data were students’ writing on recount text. The subject of this research was all students’ writing and the objects of this study were the errors found in the students’ recount text. The findings are as below. First, based on surface strategy taxonomy, misformation errors were found at the rate of 58.7%, while omission is committed for 19.4%. Addition errors are at 13%, and misordering were performed 8.9% in total. Second, based on communicative effect taxonomy, the local error was produced 58.25% while the global error was performed for 41.74%. It can be concluded that students’ error in writing recount texts is generally misormation and local error. As further recommendation, it is best to figure out the different text or discourse to explore more about errors produced by students at middle school.